Fibrinogen, Factor VII and PAI-1 Genotypes and the Risk of Coronary and Peripheral Atherosclerosis: Edinburgh Artery Study - Lee, A. J.; Fowkes, F. G. R.; Lowe, G. D. O.; Connor, J. M.; Rumley, A. (Thrombosis and Haemostasis, 1999)
There are now many epidemiological studies that have shown a relationship between haemostatic factors and subsequent risk of both coronary and peripheral arterial disease. However, there is less information on the association between genetic variation in these factors and the risks of coronary and peripheral arterial disease. As part of the five-year follow-up of the Edinburgh Artery Study, polymorphisms of the fibrinogen (-455G/A), factor VII (R/Q353) and PAI-1 (HindIII) genes were measured in men and women aged 60-79 years, together with their plasma levels. Using widely accepted criteria, 88 subjects were identified as having peripheral arterial disease (PAD), 195 having coronary artery disease (CAD) and 423 subjects comprised a “healthy” group. The -455AA genotype of the fibrinogen gene was found to be more frequent among those subjects with PAD. This genotype also showed the highest plasma fibrinogen levels in both disease groups and in the healthy group. Using logistic regression, after adjustment for age, sex, smoking and plasma level, the -455AA genotype was associated with over twice the risk of PAD compared with the -455GG genotype, the odds ratio reaching marginal significance (p″0.10). Combining those with genotype -455AA with the heterozygotes in order to increase the power of the study resulted in a more significant multiple-adjusted risk of PAD (p″0.05). These data provide evidence that a polymorphism of the β fibrinogen gene is associated with an increased risk of peripheral atherosclerosis.